Using Electroplating Sludge and Rice Husk Biochar for the Photocatalytic Degradation of Phenols in Aqueous Environment - Minh Trang, Hoang; Thi Mai, Nguyen; Xuan Huan, Nguyen; Thi Diu, Dinh (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2SDO - 10.25073/2588-1094/vnuees.5417, 2025)
In this study, electroplating sludge and rice husk were utilized for the synthesis of photocatalytic material for the degradation of phenols in aqueous environment. The characterization of the synthesized material was evaluated using EDX, SEM, and FTIR. The results indicated the presence of C, O, and other elements such as Ca, Si, Ni, Zn, Cu, Al, and Fe along with the porous structure of the biochar, which contributed to the removal of phenols. The influence of various parameters, including pH (3-10) and catalyst dosage (0.8 - 2 mg/L), was investigated. The results showed that after 240 mins of reaction, a degradation effectiveness of 54% was achieved for a phenol concentration of 20 ppm with the catalytic dosage of 1.5 mg/L under UVC irradiation. This study offers a flexible and scalable framework for the reuse of electroplating sludge in an environmentally friendly manner. By repurposing the treated waste as catalyst for phenol breakdown, the simple technique offers broad adoption while improving sustainability and resource efficiency.